Esterification of Jatropha curcas hydrolysate using powdered niobic acid catalyst - Mohammed, Nurudeen Ishola; Kabbashi, Nassereldeen Ahmed; Alam, Md Zahangir; Mirghani, Mohamed Elwathig Saeed (Taiwan Institute of Chemical Engineers, 2016)
In this study, free fatty acids (hydrolysate) produced from hydrolysis of Jatropha curcas oil was used for biodiesel production. The hydrolysate was esterified with methanol as the acyl acceptor in the presence of powdered calcined niobic acid catalyst. FT-IR analysis of the fluffy powdered catalyst was carried out to determine the conformational changes in the spectra of the catalyst. Results of the effect of various parameters tested revealed that powdered niobic acid is a viable catalyst in esterification of hydrolysate (FFA) for biodiesel synthesis. The biodiesel yield and FFA conversion were found to be 98% and 100% respectively. Kinetics data revealed that the esterification approach in the study obey a pseudo first order reaction under the investigated experimental study, hence, a lower activation energy value of 21.26 kJ/mol was recorded relative to higher values for transesterification process available in literature